Association of the DRD2 gene Taq1A polymorphism and alcoholism: a meta-analysis of case-control studies and evidence of publication bias. - Munafo, MR; Matheson, I; Flint, J (2007)
We investigated the association of the dopamine D2 receptor (DRD2) Taq1A polymorphism and alcoholism, using meta-analytic techniques, and specifically undertook an investigation of possible publication bias. Potential publication bias represents a genuine risk to the integrity of published research, but its impact has rarely been documented. We observed a small effect of the DRD2 Taq1A polymorphism on risk of alcoholism, indicating increased alcoholism in individuals possessing the A1 allele of the Taq1A polymorphism (OR=1.21, 95% CI 1.13-1.30, P<0.001). This association remained significant when data from samples of European and East Asian ancestry were analyzed separately. We did not find evidence for association in high-severity alcoholism compared to low-severity alcoholism. Removing the first published study significantly reduced the magnitude of the pooled effect size estimate, although the association remained significant. In addition, we observed evidence for possible publication bias and for the strength of individual study effect size to be inversely related to year of publication. These results support the association of the DRD2 Taq1A polymorphism with alcoholism. This conclusion is qualified by the possibility of publication bias in the literature and the observed between-study heterogeneity, which indicates that the observed association may differ in strength between populations or may not exist at all in some populations.